2007
DOI: 10.1089/adt.2006.029
|View full text |Cite
|
Sign up to set email alerts
|

A High Throughput Luminescent Assay for Glycogen Synthase Kinase-3β Inhibitors

Abstract: A high throughput luminescent assay based on the Kinase-Glo() system (Promega, Madison, WI) has been developed for screening against glycogen synthase kinase-3beta (GSK-3beta). Careful optimization of assay parameters allowed us to develop a robust, reproducible, and sensitive assay. Its usefulness has been demonstrated in a high throughput screening run when screening 55,000 compounds. This campaign yielded five chemical classes of hits, including several highly potent GSK-3beta inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(112 citation statements)
references
References 18 publications
3
106
0
1
Order By: Relevance
“…Enzyme assays to determine GSK-3b activity were carried out as described by Baki et al 23 Measurement of AchE activity was adapted from the colorimetric assay described by Ellman et al 24 for a microplate test system. Reverse transcriptase activity was assayed using a colorimetric reverse transcriptase enzyme-linked immunosorbent assay kit (Cat.…”
Section: Biological Activitymentioning
confidence: 99%
“…Enzyme assays to determine GSK-3b activity were carried out as described by Baki et al 23 Measurement of AchE activity was adapted from the colorimetric assay described by Ellman et al 24 for a microplate test system. Reverse transcriptase activity was assayed using a colorimetric reverse transcriptase enzyme-linked immunosorbent assay kit (Cat.…”
Section: Biological Activitymentioning
confidence: 99%
“…Overall, these results indicate that 6-gingerol exhibited protective effects on apoptosis induced by A␤1-42 in cultured PC12 cells by reducing oxidative stress and inflammatory responses, suppressing the activation of GSK-3␤ and enhancing the activation of Akt, thereby exerting neuroprotective effects. Kim DS et al [28] have isolated four shogaols from the roots of Zingiber officinale that protect IMR32 human neuroblastoma and normal human umbilical vein endothelial cells from beta-amyloid (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) insult at EC 50 = 4.5-81 M. In their further studies, they have synthesized ten shogaols to evaluate the importance of the side-chain length in protecting cells from amyloid betaA(1-42) insult using PC12 rat pheochromocytoma and IMR-32 human neuroblastoma cells [29]. Taking into account this in vitro studies Moon M et al [30] has shown 6-shogaol was capable to attenuate neuroinflammation and cognitive deficits in animal models of dementia in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Kinase-Glo assays were performed in assay buffer using black 96-well plates as described previously by Baki et al [25] In a typical assay, 10 l (10 M) of test compound (dissolved in dimethyl sulfoxide [DMSO] at 1 mM concentration and diluted in advance in assay buffer to the desired concentration) and 10 l (20 ng) of enzyme were added to each well followed by 20 l of assay buffer containing 25 M substrate and 1 M ATP. The final DMSO concentration in the reaction mixture did not exceed 1%.…”
Section: Gsk-3β Activitymentioning
confidence: 99%
“…The antimicrobial assays were performed as described by Helaly et al 23 To determine the cytotoxicity of compound 1, the sensitivity of the cell line NIH-3T3 was evaluated by monitoring the metabolic activity using the CellTiter-Blue À Cell Viability Assay (Promega, Mannheim, Germany). The cultivation of the cell line and the bioassay were performed as described by Schneemann et al 24 GSK-3b inhibition with compound 1 was determined in an in vitro assay adapted from a luminescent assay described by Baki et al 25 …”
Section: Producing Organism and Its Classificationmentioning
confidence: 99%